2011
DOI: 10.1063/1.3525461
|View full text |Cite
|
Sign up to set email alerts
|

A polarizable ion model for the structure of molten CuI

Abstract: The results are reported of the molecular dynamics simulations of the coherent static structure factor of molten CuI at 938 K using a polarizable ion model. This model is based on a rigid ion potential to which the many body interactions due to the anions induced polarization are added. The calculated structure factor reproduces the clear sharp prepeak observed in neutron diffraction data. The corresponding partial structure factors and the related radial distribution functions calculated by molecular dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…36-38 They were also used by Trullas and co-worker to study a series of silver and copper halides, [39][40][41][42][43] and the PIM model now is implemented in the CP2K code. 44 Going back to the case of oxides, when attention is restricted to a single phase or where similar materials are being compared it is often sufficient to neglect the full complexity of the AIM model, and we have also successfully used some PIM-type potentials in the case of amorphous GeO 2 45,46 and of doped zirconia crystals.…”
Section: Interaction Potentialsmentioning
confidence: 99%
“…36-38 They were also used by Trullas and co-worker to study a series of silver and copper halides, [39][40][41][42][43] and the PIM model now is implemented in the CP2K code. 44 Going back to the case of oxides, when attention is restricted to a single phase or where similar materials are being compared it is often sufficient to neglect the full complexity of the AIM model, and we have also successfully used some PIM-type potentials in the case of amorphous GeO 2 45,46 and of doped zirconia crystals.…”
Section: Interaction Potentialsmentioning
confidence: 99%
“…It is difficult to explain why the E a for molten CuI is larger than that for AgI by considering the difference in the ionic size and mass between Ag and Cu, because an Ag ion is larger and heavier than a Cu ion, which seems to be a disadvantage for the ionic diffusion. Furthermore, the valence charges of Ag and Cu ions are almost the same [12,13]. However, the concentration dependence of E a for (AgI) 1-x (CuI) x mixtures observed in this study would not be the error, because the similar behavior has also been reported for the solid solution of AgI-CuI system [5].…”
mentioning
confidence: 48%
“…Furthermore, weak covalencies of cation-cation pairs have also been reported [14,15], and finally the resulting first correlation lengths of cationcation and cation-I correlations are different for molten AgI and CuI [16]. Moreover, it has been reported that the electric field generated from the dipole-moment of anions affects the liquid structure and cationic diffusion in molten Ag and Cu halides [12,13,[17][18][19]. These complex properties of Ag and Cu halides compared to typical molten salts might be associated with the activation energy in AgI-CuI system.…”
mentioning
confidence: 99%
“…Although we used the rigid ion model in this study, if we consider a polarizable ion model, the cation diffusion would become large. However, polarization effects on NaI, RbI, and their mixture would be weak compared to silver (or cupper) halides [13][14][15][16][17][18][19][20] and zinc halides [21,22]. Ciccotti et al have reported that D Na and D I for pure NaI at 1081K are 9.4 × 10 -5 and 6.8 × 10 -5 cm 2 /s, respectively [3].…”
Section: " ! "mentioning
confidence: 99%